Peran Pemanfaatan E-Commerce dalam Menumbuhkan Jiwa Kewirausahaan Mahasiswa Universitas Pgri Madiun - Aliffah Septia Wardani; Yahya Reka Wirawan; Wikanso Wikanso; Ninik Srijani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe and analyze the role and contribution of e-commerce utilization in fostering the entrepreneurial spirit of students at PGRI Madiun University (UNIPMA), as well as to identify the supporting factors and challenges faced by students in running digital businesses within the campus environment. This study employs a qualitative approach with a phenomenological research design. The informants consisted of 15 active students from various faculties at UNIPMA, selected using a purposive sampling technique based on the criterion that they had utilized e-commerce platforms as a means of independent entrepreneurship. Data were collected through in-depth interviews and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana. Data validity was tested through source, technique, and time triangulation. The findings indicate that the utilization of e-commerce significantly contributes to fostering students' entrepreneurial spirit through six main characteristics: increased self-confidence, the development of innovative and resilient attitudes, enhanced networking skills, the courage to take calculated risks, the transformation of mindset from consumer to producer, and the learning of emotional management and resilience when facing business failure. The main supporting factors include academic support, entrepreneurship-oriented curricula, technological infrastructure, social support, access to capital, digital payment systems, and marketplace training. Meanwhile, the challenges encountered include psychological challenges (fear of failure and stress), social barriers in the form of stigma, intense market competition due to platform algorithms, technical issues related to internet connectivity, and limitations in operational capital and financial management. Overall, the integration of e-commerce has proven effective as a practical laboratory for developing resilient digital entrepreneurial character.